Mobilidade urbana sustentável e polos geradores de viagens : análise da mobilidade não motorizada e do transporte público - Alves, Priscilla (2015)
Observing the historical and spatial development process of Brazilian cities, it can be seen that the actions were planned with a focusing on motoring and individual circulation (specially automobiles and motorcycles) over the urban mobility nonmotorized (walkers and cyclists) and public transportation. As a result of this process, we can see cities with impaired quality of life and where we find few spaces for nonmotorized traffic (on foot or by bicycles), long traffic jams, public transport decline, increased levels of pollution, conflicts and traffic accidents. This fact has a negative impact for sustainable urban mobility, because the spaces are now not accessible and they don\'t offer a safe and adequate infrastructure for the displacements on foot, by bicycle or public transport. The Trips Generators are enterprises that settle in urban areas and, most of the time, they change the dynamics of urban mobility and accessibility of the area of influence where they are inserted and it compromises the quality and sustainability of urban mobility. The main objective is to analyze, from a quantitative point of view (Measures for Sustainable Urban Mobility - MSUM) and qualitative (technical and diagnostic evaluation), the road infrastructure conditions offered to non-motorized modes (walkers and cyclists) and public transportation in Trips Generators areas in Uberlândia-MG. The methodology involves a direct search (data collection obtained through field research and semi-structured interviews) and indirect research with collecting data on public agencies and academic papers. The results confirmed the hypothesis on the thesis that interventions and actions that occur in the areas of Trip Generators influences don\'t consider the infrastructure needs and appropriate conditions for sustainable and inclusive urban mobility that considers as a priority non-motorized modes (walkers and cyclists) and public transportation. Both in quantitative approach (MSUM) and the qualitative approach (technical and diagnostic evaluation) the results showed that the infrastructure of urban mobility in the areas of influence of the analyzed Trip Generators don\'t meet satisfactorily and safely displacement on foot, by bicycle and by public transport, it is therefore necessary interventions.